Ada yang bisa ngerjainnya ga?
![](https://id-static.z-dn.net/files/d8a/c598e6061f4eaae339ce790ac4828895.jpg)
Jawab:
(A). 9
Penjelasan dengan langkah-langkah:
[tex]\frac{35x-11}{3x(x-1)} = \frac{A(3x-1)+ B(x)}{x(3x-1)}[/tex]
[tex]\frac{35x-11}{3x(x-1)} = \frac{3Ax-A+ Bx}{3x^2-3}[/tex]
[tex]\frac{35x-11}{3x(x-1)} = \frac{3Ax-A+ Bx}{3x(x-1)}[/tex]
[tex]\frac{35x-11}{3} = \frac{3Ax-A+ Bx}{3}[/tex]
[tex]35x-11=3Ax-A+Bx[/tex]
- A = - 11
A = 11
(3A + B)x = 35x
3A + B = 35
3(11) + B = 35
B = 35 - 33 = 2
Maka, A - B = 11 - 2 = 9 (A)
[answer.2.content]